Below-Background Ionizing Radiation as an Environmental Cue for Bacteria - Castillo, Hugo; Smith, Geoffrey B. (Frontiers in Microbiology, 2017)
All organisms on earth grow under the influence of a natural and relatively constant dose of ionizing radiation referred to as background radiation, and so cells have different mechanisms to prevent the accumulation of damage caused by its different components. However, current knowledge of the deleterious effects of radiation on cells is based on the exposure to acute and high or to chronic, above background doses of radiation and therefore is not appropriate to explain the cellular and biochemical mechanisms that cells employ to sense and respond to chronic below-background levels. Studies at below-background radiation doses can provide insight into the biological role of radiation, as suggested by several examples of what appears to be a stress response in cells grown at doses that range from 10 to 70 times lower than background. Here we discuss some of the technical constraints to shield cells from radiation to below-background levels, as well as different approaches used to detect and measure responses to such unusual environmental conditions. Then we present data from Shewanella oneidensis and Deinococcus radiodurans experiments that show how two taxonomically distant bacterial species sense and respond to unnaturally low levels of radiation. In brief, we grew S. oneidensis and D. radiodurans in liquid culture at dose rates of 62.75 (control) and 0.89 (treatment) nGy hr-1 (including radon) for up to 72 hours and measured cell density and the expression of stress-related genes. Our results suggest that a stress response is triggered in the absence of normal levels of radiation.